2015
DOI: 10.1002/ceat.201500160
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Pressure Drop and Heat Transfer Coefficient in Corrugated Tubes

Abstract: Single-structured tubes (SSTs) and cross-structured tubes (CSTs) with helix-based structures are investigated with respect to their heat transfer properties and pressure drop based on the measurements of a non-isothermal gas flow inside the tubes. The examined Reynolds number range corresponds to relevant shell-andtube heat exchanger applications. After a detailed description of the measuring methods used, the test facilities and their validation-appropriate wall geometries with a high potential for heat trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…While concave structuring brings significant heat transfer advantages, this does not occur with convex structuring. This behaviour corresponds with the results of [11,12] and confirms the strong dependence of heat transfer on the structuring.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While concave structuring brings significant heat transfer advantages, this does not occur with convex structuring. This behaviour corresponds with the results of [11,12] and confirms the strong dependence of heat transfer on the structuring.…”
Section: Discussionsupporting
confidence: 89%
“…Further numerical studies [9,10] have shown that an increase in heat transfer performance is associated with structuring. Further possibilities are the use of spirally structured [11] or corrugated [12] tubes. In both cases, the heat transfer coefficient of the structured surface increases significantly compared to a smooth surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, single spirally corrugated tubes showed 1.66 times higher Nu value regardless of Re. Moreover, increase in pressure drop, as concluded in [23], depends on the corrugation angle in single spirally corrugated tubes while in cross-spirally corrugated tubes pressure drop rose significantly regardless of the corrugation angle. Pethkool et al, [17] reported up to 300 % higher Nu values for helically corrugated tubes with the increase in friction factor by 1.93 when compared with a smooth tube.…”
Section: Introductionmentioning
confidence: 61%
“…The Authors also concluded that the combination of the two heat transfer techniques is more effective than each of them separately. Mac Nelly et al, [23] investigated single spirally corrugated and cross spirally corrugated tubes using laboratory air in the Re range 4000 to 20000 with a Prandlt number (Pr) lower than 1. The Authors concluded that Nusselt number (Nu) increases up to 1.88 times in crossspirally corrugated tubes with increasing Re when compared to a straight one.…”
Section: Introductionmentioning
confidence: 99%
“…5a). Auch hinsichtlich des steigenden Druckverlustes beim Drallrohr gilt dies als ein vielversprechendes Ergebnis 16.…”
Section: Ergebnisseunclassified